Prevalence of musculoskeletal disorders among Polish white-collar workers: the role of physical activity and risk factors - Grabara, Małgorzata (Frontiers in Public Health, 2025)
ObjectiveThis study evaluated the prevalence of self-reported musculoskeletal disorders (MSDs) among white-collar workers and investigated their associations with physical activity (PA) levels, time spent sitting, sleep duration, and BMI.MethodsThe study included 440 white-collar workers (355 female and 85 male) aged 20–64 years, from randomly selected public institutions, companies, and corporations in the Upper Silesia region, Poland. Participants completed the Nordic Musculoskeletal Questionnaire and the Seven-Day Physical Activity Recall. Statistical analysis included comparisons of PA between workers with and without MSDs and between genders, correlations between MSDs, PA, and sleep duration, and logistic regression assessing associations between potential predictors and MSD presence. Independent variables included age, BMI, daily and occupational sitting time, sleep duration, and PA.ResultsThe 12-month prevalence of MSDs was highest for lower back pain (65.9%), neck pain (59.8%), and upper back pain (43.9%), with a similar pattern observed over 7 days. Workers reporting neck pain over the past 12 months engaged in significantly less vigorous PA and high vigorous PA compared to those without neck pain (p = 0.019, r = 0.11), while those with knee pain reported higher levels of moderate PA (p = 0.018, r = 0.11). Age and BMI significantly influenced pain in multiple regions, including the neck, shoulder, back, hip/thigh, knee, and ankle/foot. Daily sitting time was a significant predictor for most MSDs, except for hip pain, while sitting during work specifically predicted lower back pain over 12 months. Each additional year of age, unit increase in BMI, and hour of sitting increased the likelihood of pain. Sleep duration and PA levels were not significant predictors.ConclusionThese findings emphasize the importance of BMI management and reducing prolonged sitting as key workplace interventions, particularly in sedentary occupations.